Behavior-Driven Gamification Framework for Enhancing Health Insurance Engagement Using TOGAF-Based Business Architecture - Dyah Ayu Arditya; Richardus Eko Indrajit; Erick Dazki (Politeknik Pertanian Negeri Samarinda, 2026)
Health insurance providers face significant challenges in engaging policyholders and encouraging preventive health behaviors. Traditional engagement methods often lead to low participation, reducing the effectiveness of wellness programs and increasing long-term healthcare costs. This paper presents a behavior-driven gamification framework designed to enhance policyholder engagement within the health insurance sector, utilizing a TOGAF-based business architecture approach. By integrating the principles of behavioral science with game mechanics, this model aims to motivate policyholders to actively participate in their health management through personalized, interactive experiences. The application of TOGAF’s Architecture Development Method (ADM) ensures that the gamification framework is aligned with business objectives, operational processes, and technological infrastructure, providing a sustainable and scalable solution for health insurers. The proposed framework enhances customer engagement, improves health outcomes, and reduces operational costs by incentivizing healthy behaviors, fostering a more proactive and satisfied customer base. This research contributes to the growing field of digital health innovation and offers a strategic roadmap for integrating gamification within health insurance systems.